# Calculator search results

Formula
Solve the equation
Calculate the differentiation
$\gamma = 3x+2$
$x = \dfrac { 1 } { 3 } \gamma - \dfrac { 2 } { 3 }$
 Solve a solution to $x$
$\gamma = \color{#FF6800}{ 3 } \color{#FF6800}{ x } + 2$
 Move $x$ term to the left side and change the sign 
$\gamma \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } = 2$
$\color{#FF6800}{ \gamma } - 3 x = 2$
 Move the rest of the expression except $x$ term to the right side and replace the sign 
$- 3 x = 2 \color{#FF6800}{ - } \color{#FF6800}{ \gamma }$
$- 3 x = \color{#FF6800}{ 2 } \color{#FF6800}{ - } \color{#FF6800}{ \gamma }$
 Organize the expression 
$- 3 x = \color{#FF6800}{ - } \color{#FF6800}{ \gamma } \color{#FF6800}{ + } \color{#FF6800}{ 2 }$
$\color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ \gamma } \color{#FF6800}{ + } \color{#FF6800}{ 2 }$
 Change the sign of both sides of the equation 
$3 x = \gamma - 2$
$\color{#FF6800}{ 3 } \color{#FF6800}{ x } = \color{#FF6800}{ \gamma } \color{#FF6800}{ - } \color{#FF6800}{ 2 }$
 Divide both sides by the same number 
$\color{#FF6800}{ x } = \left ( \color{#FF6800}{ \gamma } \color{#FF6800}{ - } \color{#FF6800}{ 2 } \right ) \color{#FF6800}{ \div } \color{#FF6800}{ 3 }$
$x = \left ( \gamma - 2 \right ) \color{#FF6800}{ \div } \color{#FF6800}{ 3 }$
 Convert division to multiplication 
$x = \left ( \gamma - 2 \right ) \color{#FF6800}{ \times } \color{#FF6800}{ \dfrac { 1 } { 3 } }$
$x = \left ( \color{#FF6800}{ \gamma } \color{#FF6800}{ - } \color{#FF6800}{ 2 } \right ) \color{#FF6800}{ \times } \color{#FF6800}{ \dfrac { 1 } { 3 } }$
 Multiply each term in parentheses by $\dfrac { 1 } { 3 }$
$x = \color{#FF6800}{ \dfrac { 1 } { 3 } } \color{#FF6800}{ \gamma } \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ \times } \color{#FF6800}{ \dfrac { 1 } { 3 } }$
$x = \dfrac { 1 } { 3 } \gamma \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ \times } \color{#FF6800}{ \dfrac { 1 } { 3 } }$
 Calculate the product of rational numbers 
$x = \dfrac { 1 } { 3 } \gamma \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 2 } { 3 } }$
$\dfrac {d } {d x } {\left( \gamma \right)} = 3$
Calculate the differentiation of the logarithmic function
$\dfrac {d } {d \color{#FF6800}{ x } } {\left( \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 2 } \right)}$
 Calculate the differentiation 
$\color{#FF6800}{ 3 }$
Have you found the solution you wanted?
Try again
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture